Policy issues and priorities for ILCA technology research - Shapiro, Barry I. (International Livestock Centre for Africa, 1993)
Animal agriculture can add to agricultural development through income generation, intensification, foreign exchange earnings and non-agricultural development. The primary justification for being concerned with animal agricultural in sub-Saharan Africa at present is the need to increase farmer incomes. Technological change is the primary means of raising farmer incomes. However, while new technology is a necessary ingredient in the process of agircultural development, it is not sufficient without conductive policy. This paper looks at policy issues and priorities for ILCA technology research. It discusses the justificaiton for technology policy research, the nature of government policies in SSA, priority species and commodities for technology policy research and technology transfer research. Identifying appropriate policies and their effects on alternative technologies is also discussed.